The Brazilian credit market: Recent developments and impact on inequality - Daniela Magalh\~aes Prates; Adriana Nunes Ferreira; Daniela Gorayeb (International Labour Organization (ILO), 2015)
The aim of this paper is analyzing the evolution of the Brazilian credit market from 2003 to 2011 and its impact on inequality in Brazil. The arguments are organized as follows. After an introductory section, the second one presents the determinants and the general trends of the banking credit market between December 2003 and December 2011, while the third section analyses the extent to which employment and incomes in the banking sector might have contributed to reduce the inequality in Brazil. The paper closes with some final remarks on the lessons that can be drawn from the Brazilian experience.
Keywords: 330; banking; bank; credit; income distribution; Brazil